A study of clinker microstructure using scanning electron microscope - Mohd Sobri, Idris; Shamsul Baharin, Jamaludin; Che Mohd Ruzaidi, Ghazali; Kamarudin, Hussin; Khairul Nizar, Ismail (Malaysian Institute for Nuclear Technology Research (MINT), 2011)
International Conference on X-Ray and Related Techniques in Research and Industry 2006 (ICXRI 2006), organized by Malaysian Institute for Nuclear Technology Research, from 29th - 30th November 2006 at Palm Garden Hotel IOI Resort, Putrajaya.